Information Seeking Behaviour of the Users of Hardayal Municipal Heritage Public Library (Chandni Chowk ) : A Study - Pramod Kumar Paswan (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The purpose of the study to investigate the information needs and information seeking behavior of Hardayal Municipal Heritage Public Library. In this paper survey method was used for collection data. The data were collected 260 from users of Hardayal Municipal Heritage Public Library. It was found that male users are more use of information needs and information seeking behavior than female. Mostly users come for preparation of competitive exam, up to date knowledge and also use of library services. Majority users get located information with help of library staff assistance of library. Users get information easily but in some condition also being faced problem i.e. inadequate collection, Lack of skills required to search information, Lack of guidance support of professors and library staff etc.